Subdiffraction nanofocusing of circularly polarized light with a plasmonic cavity lens. Issue 19 (18th April 2019) - Luo, Yunfei; Kong, Weijie; Zhao, Chengwei; Liu, Kaipeng; Pu, Mingbo; Wang, Changtao; Luo, Xiangang
Abstract : Nanofocusing beyond the diffraction limit could be achieved by a plasmonic cavity lens under circularly polarized light illumination. Abstract : Nanofocusing beyond the diffraction limit has received a significant amount of attention in recent years due to its versatility. In this paper, subdiffraction nanofocusing of circularly polarized light is achieved in a plasmonic cavity lens by constructive interference of plasmonic waveguide modes launched by a spiral slot. By employing a plasmonic cavity lens composed of a metal–insulator–metal (MIM) waveguide, the plasmonic mode wavelength could be suppressed efficiently and thus a deep subwavelength focal spot could be attained. Simulated and lithography experimental results indicate that a focal spot with 60 nm size and 30 nm depth of focus could be produced in a photoresist under laser illumination with 375 nm wavelength. Moreover, the plasmonic cavity lens could tolerate a maximum air gap between the mask and the lens of 40 nm, which facilitates practical applications. Additionally, defocusing would happen for a spiral slot with opposite chirality. This design provides a simple solution for deep subwavelength light confinement and may find applications in nanolithography, super resolution imaging, high density data storage, etc.